FAKTOR YANG MEMPENGARUHI TERJADINYA BENCANA BANJIR DI KECAMATAN BONJOL - resma yani; Helfia Edial (JURNAL BUANA, 2021)
This study aims to: 1) Know the land use of the Masang Kiri sub-watershed. 2) Knowing the rain intensity of Masang Kri sub-watershed. 3) Knowing the carrying capacity of the Masang river. 4) To know the dominant factor that resulted in the flood disaster in Bonjol District. This research is a quantitative descriptive study. The method used is the rational method. The results of this study are 1) forest land use dominates the Masang sub-watershed with a percentage of 74.7% and the least is dry land / field with a percentage of 0.2%. 2 Rain intensity value for 1 year return period is 16.48 mm / hour. 3) the carrying capacity of the Masang River is 363,528 m3 / second, while the results of the calculation of the peak discharge when the maximum rain occurs in a 1 year return period is 385.18 m3 / second. 4) The dominant factor that causes flood disaster in Bonjol District is the rain intensity factor.